Analisis Marketing 3.0 Sebagai Rekomendasi Peningkatan Kunjungan Unit Rawat Inap Di Rumah Sakit Islam Surabaya A. Yani - Atika Nurmawaddah, Lia (CV RIFAINSTITUT, 2022)
Bor in the inpatient unit at Surabaya Islamic Hospital A. Yani is still very low (30%) compared to the target BOR according to the Ministry of Health of the Republic of Indonesia (60% – 85%) in the last 3 months. The purpose of this study was to analyze marketing 3.0 as a recommendation for increasing visits in the inpatient unit of Surabaya Islamic Hospital A.Yani. This research is a quantitative descriptive research with a cross-sectional approach. Data taken in May – June 2022. The data used is primary data using a questionnaire in the form of GoogleForm. The population in this study was part of the inpatient unit patients at the Surabaya A. Yani Islamic Hospital, with a sample of 80 taken by simple random sampling. The results of this study show that A. Yani Islamic Hospital has sufficiently implemented marketing 3.0 well. The analysis on the results of the questionnaire obtained several recommendations for visiting inpatient units based on marketing 3.0. This marketing recommendation is expected to increase inpatient visits at the Surabaya A. Yani Islamic Hospital.